Diabetic neuropathic pain induced by streptozotocin alters the expression profile of non-coding RNAs in the spinal cord of mice as determined by sequencing analysis - He, Jian (Exp Ther Med, 2021)
Diabetic neuropathic pain (DNP) is one of the most serious complications of diabetes. Patients with DNP always exhibit spontaneous and stimulus-evoked pain. However, the pathogenesis of DNP remains to be fully elucidated. Non-coding RNAs (ncRNAs) serve important roles in several cellular processes and dysregulated expression may result in the development of several diseases, including DNP. Although ncRNAs have been suggested to be involved in the pathogenesis of DNP, their precise roles remain to be determined. In the present study, sequencing analysis was used to investigate the expression patterns of coding genes, microRNAs (miRNAs), long ncRNAs (lncRNAs) and circular RNAs (circRNAs) in the spinal cord of mice with streptozotocin (STZ)-induced DNP. A total of 30 mRNAs, 148 miRNAs, 9 lncRNAs and 135 circRNAs exhibited signiﬁcantly dysregulated expression 42 days after STZ injection. Functional enrichment analysis indicated that protein digestion and absorption pathways were the most signiﬁcantly affected pathways of the differentially expressed (DE) mRNAs. The Rap1 signaling pathway, human T-lymphotropic virus-I infection and the MAPK signaling pathway were the three most signiﬁcant pathways of the DE miRNAs. A total of 2,118 distinct circRNAs were identiﬁed and the length of the majority of the circRNAs was <1,000 nucleotides (nt) (1,552 circRNAs were >1,000 nt) with a median length of 620 nt. In the present study, the expression characteristics of coding genes, miRNAs, lncRNAs and circRNAs in DNP mice were determined; it paves the road for further studies on the mechanisms associated with DNP and potentially facilitates the discovery of novel ncRNAs for therapeutic targeting in the management of DNP.